Terror Narrative: Representing State Violence in Modern Indonesian Literature - Ferdinal, Ferdinal (OKARA: Jurnal Bahasa dan Sastra, 2021)
Literature and society are a way of looking at problems in society. Literature not only functions as entertainment, but it may also represent socio-political problems. Some literary works even carry more roles as both a reflection of such issues and a means of protest against them, including human rights violations. This paper examines how Indonesian literature has reflected human rights breaches, such as oppression in Indonesia during the New Order era. This qualitative research was conducted through direct documentation. The research revealed that the regime punished any individuals, groups, or institutions which tried to challenge its policy by the name of national stability. Some writers, such as Putu Wijaya, used anecdotes to protest against such oppression. He was a prolific Indonesian writer whose works often expose socio-political issues, such as human rights violations in Indonesia. His writings suggest his disagreement with such abuses. The three short stories investigated here "Sket," "Mulut," and "Rakyat" represent Putu Wijaya’s dissent with the violence performed by the apparatus of the regime. Playing his role as a literary activist, Putu uses these stories to remind rights perpetrators that such cases as seen in the stories have taken place and might take place somewhere in Indonesia.